The Correlation between Islam and Globalization According to the Maudhu’i Interpretation - Nurafni Alva Prasanti; Priscilla Elsya Adila; Rik’an Mughiry Rosyadi; Asep Abdul Muhyi (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Globalization is a phenomenon of change in today's world that cannot be avoided or prevented. It is a process of modernization and unification of the world in terms of communication, religion, ideology, economy, culture, etc. This paper aims to explain the relationship between globalization and Islam. This paper will explain the characteristics of Islam and globalization, its impact, its existence in the present day and its interpretation in the Qur'an using the maudhu'i method of interpretation. The research method taken is qualitative through a descriptive approach using library research data collection techniques. The results found are the word globalization is represented with al-'alamiin in Qs. Al-Anbiya verse 107 and Qs. Al-Furqan ayat 1. The term